2010
DOI: 10.3382/ps.2010-00757
|View full text |Cite
|
Sign up to set email alerts
|

Standardized ileal amino acid digestibility in dry-extruded expelled soybean meal, extruded canola seed-pea, feather meal, and poultry by-product meal for broiler chickens

Abstract: Ileal digestibility of amino acids (AA) in dry-extruded expelled soybean meal (DESBM), co-extruded canola seed-pea blend (ECSP, 50:50 wt/wt basis), poultry by-product meal (PBPM), and feather meal (FM) were determined in broiler chicks. For each ingredient, 5 samples each collected on different occasions were evaluated. Birds (n = 180 for each sample) were fed a commercial starter diet from d 1 to 15 of age followed by the test diets from d 15 to 21. Dry-extruded expelled soybean meal, ECSP, PBPM, and FM were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
5
17
0
2
Order By: Relevance
“…The inorganic matter (ash) was low in most ingredients, except for the fish processing by-product peptides (FishP) and the poultry byproduct meal (POULT). These results were expected, as these animal The amino acid contents of the whole test ingredients were similar to the values previously reported in the literature (Allan et al, 2000;Bandegan et al, 2010;Guimaraes et al, 2008;NRC, 2011). Compared to a reference anchovy fishmeal (5-01-985; NRC, 2011), which is considered to have the best amino acid profile for fish nutrition, test ingredients were short in some essential amino acids and rich in others.…”
Section: Discussionsupporting
confidence: 91%
“…The inorganic matter (ash) was low in most ingredients, except for the fish processing by-product peptides (FishP) and the poultry byproduct meal (POULT). These results were expected, as these animal The amino acid contents of the whole test ingredients were similar to the values previously reported in the literature (Allan et al, 2000;Bandegan et al, 2010;Guimaraes et al, 2008;NRC, 2011). Compared to a reference anchovy fishmeal (5-01-985; NRC, 2011), which is considered to have the best amino acid profile for fish nutrition, test ingredients were short in some essential amino acids and rich in others.…”
Section: Discussionsupporting
confidence: 91%
“…The CAID of CP and AA of the SBM were within the range reported by Pérez et al (1993), Huang et al (2005), Valencia et al (2009a) and Bandegan et al (2010), although lower than valúes reported by Ravindran et al (1999Ravindran et al ( , 2005 and higher than those reported by De Coca-Sinova et al (2008). The reasons for the differences in CAID of the AA among researchers are not known but might be related to the conditions applied during the processing of the beans as well as the methodology used, including type of marker, age of the birds, slaughter technique and segment of the ileum used to collect the samples (Rynsburger, 2009).…”
Section: Coefficients Ofapparent and Standardized Tíeal Digestibtíitysupporting
confidence: 73%
“…Adequate processing is required before soybean meal inclusion in poultry diets because under heating produces incomplete inactivation of the anti-nutritional factors whereas overheating will decrease AA availability [7,8]. The digestibility of animal by-products also depends on the type of carcass components used in their production; meat meals with a high content of organ parts tend to have lower solubility proteins, such as collagen and keratin [9,10]. Genetic variability within plant ingredients is also known to affect protein digestibility in poultry [11,12].…”
Section: Description Of Problemmentioning
confidence: 98%